Deteccion de dothiorella aesculi ahmad en mangifera indica L. en Cuba - Hidalgo, E.I.=700 1 Neninger, L.H.; Barrios, L.M.
(Es, En)
Ilus., 12 ref.
Keywords: MANGIFERA INDICA; BOTRYOSPHAERIA; SINTOMAS; DIAGNOSTICO; CUBA